Does phloem-based resistance to aphid feeding affect host-plant acceptance for reproduction? Parturition of the pea aphid, Acyrthosiphon pisum, on two near-isogenic lines of Medicago truncatula. Issue 6 (3rd July 2013) - Nam, K. Jung; Powell, G.; Hardie, J.
Abstract: Probing behaviour (prior to parturition) and parturition of two clones (PS01 and N116) of the pea aphid, Acyrthosiphon pisum on two genotypes (near-isogenic lines (NILs)) (Q174_5.13 and Q174_9.10) of Medicago truncatula were investigated using electrical penetration graph (EPG) coupled with simultaneous visual monitoring for parturition. Line Q174_5.13 has been reported to show a phloem-based resistance to feeding in the clone PS01 but to be susceptible to the clone N116, whereas Q174_9.10 has shown to be susceptible to both aphid clones. The time taken to first parturition by clone PS01 was similar on Q174_5.13 and Q174_9.10. Prior to parturition, no aphids on Q174_5.13 contacted phloem, but 5% of the aphids on Q174_9.10 showed phloem salivation (recognized by EPG pattern E1). No phloem contact was observed with aphid clone N116 on either NILs of Medicago before first parturition occurred, and the time taken to first larviposition was similar on Q174_5.13 and Q174_9.10. The results indicate that the initiation of parturition of the clone PS01 and N116 on both NILs does not require the phloem contact and seems unchanged by a phloem-based resistance mechanism to feeding on Medicago . This finding suggests that host recognition and decisions about parturition occur before phloem contact or ingestion, and act independently on R -gene-mediated resistance.